Trabeculectomy Outcomes by Supervised Trainees in a Veterans Affairs Medical Center. Issue 8 (August 2016) - Biggerstaff, Kristin S.; Vincent, Ryan D.; Lin, Albert P.; Orengo-Nania, Silvia; Frankfort, Benjamin J.
Abstract : Purpose: To evaluate the outcomes of trabeculectomy performed in an ophthalmology training program. Design: Retrospective study. Participants: A total of 160 patients undergoing trabeculectomy performed by a resident or fellow under attending supervision. Materials and Methods: Trabeculectomy surgeries performed by a supervised resident or fellow surgeon between October 2000 and April 2010 were reviewed. Success was considered to be complete or partial if intraocular pressure (IOP)-lowering medications were not or were required to achieve IOP⩽21 mm Hg, respectively. Failure was defined as IOP>21 mm Hg on 2 consecutive visits, loss of light perception vision, IOP⩽5 on 2 consecutive visits with associated visual acuity loss of ≥2 lines, or need for surgical intervention. Trabeculectomy survival was determined using Kaplan-Meier analysis through 60 months of follow-up. Main Outcome Measures: Final IOP, success/failure rate. Results: Complete success was achieved in 65 patients (41%). The average final IOP of this group was 9.1±3.7 mm Hg. Qualified success was achieved in 56 patients (35%). The average final IOP of this group was 11.5±6.4 mm Hg. At 60 months, the estimated cumulative probability of survival for complete and qualified successes was 28.9% and 63.7%, respectively. Conclusions: Among patients undergoing trabeculectomy by supervised residents or glaucoma fellows in a large Veterans Affairs Medical Center, IOP reduction was significant and similar to published studies. Trabeculectomy remains a successful intervention to lower IOP, with satisfactory success rates in the hands of trainee surgeons.